ODIA LANGUAGE, LITERATURE AND CULTURE AN INTRODUCTION - (:unkn) unknown (My University, 2019)
The aim is to give a brief introduction about Odisha, its language, the literary and cultural tradition to non-native learners of Odia.
Odia Bhasha, Sahitya o Sanskriti: Ek Parichaya
Keywords: Odia